ANALISIS FRAMING PEMBERITAAN KOMPAS.COM TENTANG COVID-19 DI DKI JAKARTA - Rosida Simatupang (Jurnal Pustaka Komunikasi, 2021)
Handling the Covid-19 virus outbreak in Indonesia since its emergence in March 2020 requires targeted policies both at the national and regional levels. The spread and handlers of the Covid-19 virus are a concern because the number is increasing dramatically. Jakarta as the capital of the country becomes a parameter for other regions in the handling of Covid-19. The outbreak of global pandemic status certainly attracted the attention of the mass media, including online media. With the ability to construct reality, online media has the power to process facts and data in such a way, in accordance with its interests. Researchers will analyze the news with framing analysis to find out the construction of Kompas.com in the news of COVID-19 in DKI Jakarta.This study aims to analyze how framing Kompas.com news about COVID-19 in DKI Jakarta. The research method used is qualitative with framing analysis of Pan and Kosicki models. The results of the study suggest that Kompas.com tends to support governor Anis Baswedan's policy of quarantine the DKI Jakarta area, then Kompas.com does not meet the principle of accuracy in running disaster journalism because it does not verify data.